Reading the history of venereal diseases in the city: Venereal disease from Surabaya, 19th-20th century - M. Moordiati (PAGEPress Publications, 2019)
This article aims to explore about venereal diseases that occurred in the city of Surabaya throughout the nineteenth to the twentieth century. Not much is known about what actually happened with the presence of venereal disease in the city of Surabaya throughout this period. Some existing sources are still always connected if the presence of venereal disease is more caused by prostitution activities as alleged during this time. Though it does not rule out the possibility if the disease is also caused by the consequences of others. This is presumably that became one of the reasons of this article to see if there are any reasons or other reasons to why the venereal disease can exist in Surabaya. Therefore the use of many sources (primary or secondary) is very important in this article to compare and differentiate between venereal diseases in the city of Surabaya and other cities.